Pengaruh Penambahan Tebon Jagung, Ampas Tahu, dan EM4 Terhadap Karakteristik Fisik dan pH Silase Centrosema pubescens - Triana, Rizky Aziz; Yanza, Yulianri Rizki; Khairani, Lizah; Setiawan, Muhammad Ariana (Jurnal Pertanian Terpadu, 2025)
This study aimed to evaluate the effect of adding EM4 starter, corn stover, and tofu dregs on the physical characteristics and pH of Centrosema pubescens (CP) silage. The study used a completely randomized design with three treatments and five replications: P1 (100% CP + starter), P2 (50% CP + 50% corn stover + starter), and P3 (50% CP + 50% tofu dregs + starter). The fermentation process was conducted for 35 days using vacuum-sealed plastic to create anaerobic conditions. Data on physical characteristics (mold presence, aroma, color, and texture) were analyzed using the Kruskal-Wallis test, followed by the Dunn Test for significant differences, while pH data were analyzed using ANOVA and Duncan Test for further analysis. The results showed that treatments significantly affected aroma, texture, and pH (p<0.05). The tofu dregs treatment produced the lowest pH, while the corn stover treatment resulted in the best texture, characterized by being dense and non-slimy. All treatments achieved the highest score for mold presence, indicating the absence of mold growth. However, the greenish-brown color produced by all treatments did not meet the optimal category. Adding EM4 starter with corn stover or tofu dregs proved effective in improving the quality of Centrosema pubescens silage by enhancing pH, texture, and the absence of mold growth, although all treatments produced a greenish-brown color that was not yet optimal.